Negative plate and battery

By designing a layered structure in the negative electrode sheet of the lithium-ion battery, using the first film layer of primary particle graphite and silicon-based material and the second film layer of secondary particle graphite, the problem of insufficient volume expansion and kinetic performance of the silicon-based negative electrode material is solved, and higher cycle stability and fast charging performance are achieved.

CN119764337AActive Publication Date: 2025-04-04JIANGSU ZENIO NEW ENERGY BATTERY TECH CO LTD

Patent Information

Application Number
CN202411804658.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-04-04
Estimated Expiration
2044-12-09

AI Technical Summary

Technical Problem

Silicon-based anode material has structural damage due to volume expansion in lithium-ion batteries, and its kinetic performance is poor, which limits its development and application.

Method used

A layered negative electrode sheet was designed. The first film layer contained primary particle graphite and silicon-based material, and the second film layer contained secondary particle graphite. By adjusting the surface density of the film layer and the mass proportion of active substances, the lithium ion distribution is optimized, and the polarization and over-embedding problems are reduced.

Benefits of technology

The film resistance, full charge rebound rate and DCR growth rate of the negative electrode sheet are significantly reduced, the stability of the electrode sheet structure is improved, and the circulation and fast charging performance of the battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764337A_ABST
    Figure CN119764337A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of batteries, in particular to a negative plate and a battery. The negative plate comprises: (a) a negative current collector; (b) a first film layer, wherein the first film layer is arranged on at least one side surface of the negative electrode current collector; the first film layer comprises a first negative electrode active substance, and the first negative electrode active substance comprises primary particle graphite and a silicon-based material; the second film layer is arranged on the surface of one side, far away from the negative electrode current collector, of the first film layer; the second film layer comprises a second negative electrode active material, and the second negative electrode active material comprises secondary particle graphite. According to the negative plate, structural damage caused by volume expansion of the silicon-based material can be reduced, and the dynamic performance can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a negative electrode sheet and a battery. Background Art

[0002] Lithium-ion batteries (LIBs), as the most widely used energy storage system, have been rapidly applied to various fields since their commercialization. In recent years, with the development of portable electronic devices and the increasing demand for electric vehicles, the energy density of current LIBs has gradually failed to meet people's needs, and the development of high-energy-density LIBs is an urgent task.

[0003] Silicon anode materials are recognized as the next generation of lithium-ion battery anode materials due to their high specific capacity and low potential. However, silicon-based materials have large volume expansion during the charging and discharging process, which can easily cause structural damage to the electrode sheet. In addition, compared with traditional lithium-ion graphite anodes, silicon anodes have poor kinetic properties. The above defects limit the development and application of silicon anode materials. Therefore, research and solutions to the expansion and kinetic problems of silicon-based anode materials and anode sheets are the core development direction of the relevant industry and academia. Summary of the invention

[0004] In view of this, the present invention provides a negative electrode sheet and a battery. The negative electrode sheet has a layered design of a negative electrode sheet active material layer containing graphite material and silicon-based material, and the primary graphite particles and silicon-based material are placed in the first film layer close to the negative electrode current collector, and the secondary graphite particles are placed in the second film layer, which can not only reduce the structural damage caused by the volume expansion of the silicon-based material, but also improve the dynamic performance; further, by adjusting the technical parameters related to the surface capacity of the first film layer and the second film layer, the surface capacity of the second film layer is slightly larger than the surface capacity of the first film layer, reducing the polarization of the entire electrode sheet, helping to alleviate the problem of over-embedding of active materials, balancing the lithium ion distribution of the first film layer and the second film layer, and improving the reversible capacity.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] In a first aspect, the present invention provides a negative electrode sheet, the negative electrode sheet comprising:

[0007] (a) negative electrode current collector;

[0008] (b) a first film layer, the first film layer is disposed on at least one side of the negative electrode current collector; the first film layer comprises a first negative electrode active material, the first negative electrode active material comprises primary graphite particles and a silicon-based material;

[0009] (c) a second film layer, the second film layer is arranged on a surface of the first film layer away from the negative electrode current collector; the second film layer includes a second negative electrode active material, and the second negative electrode active material includes secondary particle graphite.

[0010] In an embodiment of the present invention, the negative electrode sheet satisfies the following relationship:

[0011] C2×K2×L2=C1×[K1×X+G×(1-X)]×L1×α

[0012] Wherein, C2 is the coating surface density of the second film layer,

[0013] K2 is the gram capacity of secondary graphite particles in the second film layer,

[0014] L2 is the mass proportion of the second negative electrode active material in the second film layer,

[0015] C1 is the coating surface density of the first film layer,

[0016] K1 is the gram capacity of primary graphite particles in the first film layer,

[0017] X is the mass ratio of primary graphite particles in the first film layer to the first negative electrode active material, G is the gram capacity of the silicon-based material in the first film layer,

[0018] L1 is the mass proportion of the first negative electrode active material in the first film layer,

[0019] α is the correction coefficient.

[0020] In the embodiment of the present invention, the value range of K2 is 340 to 360 mAh / g.

[0021] In the implementation manner of the present invention, the value range of L2 is 95% to 97%.

[0022] In the embodiment of the present invention, the value range of K1 is 340-360 mAh / g.

[0023] In the implementation manner of the present invention, the value range of X is 0.5 to 0.97.

[0024] In the embodiment of the present invention, the value range of G is 1300-1700 mAh / g.

[0025] In the implementation manner of the present invention, the value range of L1 is 94.2% to 95.7%.

[0026] In the implementation manner of the present invention, the value range of α is 1.01 to 1.06.

[0027] Preferably, the primary graphite particles are carbon-coated primary graphite particles.

[0028] Preferably, the carbon-coated primary graphite particles have a particle coating degree of >50%, a carbon coating amount of >2%, and a particle size D 50 6~10μm.

[0029] In an embodiment of the present invention, the silicon-based material includes a silicon-oxygen material and / or a silicon-carbon composite material.

[0030] As a preference, the particle size D of the silicon-based material 50 6~10μm.

[0031] Preferably, the silicon-based material accounts for 3% to 50% of the total mass of the first negative electrode active material.

[0032] Preferably, the secondary graphite particles are carbon-coated secondary graphite particles.

[0033] Preferably, the carbon-coated secondary graphite particles have a particle coverage degree of >50% and a carbon coating amount of >2%.

[0034] In an embodiment of the present invention, the first film layer includes the following components in percentage by weight:

[0035] The first negative electrode active material is 94.2% to 95.7%;

[0036] The first conductive agent is 1.5% to 1.7%;

[0037] The first binder is 2.8% to 5%.

[0038] In an embodiment of the present invention, the second film layer includes the following components in proportion by weight:

[0039] The second negative electrode active material is 95% to 97%;

[0040] The second conductive agent is 1% to 1.5%;

[0041] The second binder is 2% to 3.5%.

[0042] Preferably, the mass proportion of the first adhesive in the first film layer is greater than the mass proportion of the second adhesive in the second film layer.

[0043] In a second aspect, the present invention provides a battery comprising the negative electrode sheet described above.

[0044] Compared with the prior art, the present invention has the following beneficial effects:

[0045] The present invention has designed a layered design for the negative electrode sheet active material layer containing graphite material and silicon-based material, placing primary graphite particles and silicon-based materials in the first film layer close to the negative electrode current collector, and placing secondary graphite particles in the second film layer. Among them, the primary graphite particles in the first film layer are mixed with silicon-based materials to increase the negative electrode gram capacity, and the primary graphite particles with high structural strength are used for mixing to reduce the structural damage caused by the volume expansion of the silicon-based material; the secondary graphite particles in the second film layer are used to improve the dynamics. Based on this design, the present invention can significantly reduce the membrane resistance, full charge rebound rate and DCR (direct current resistance) growth rate of the negative electrode sheet, effectively improve the stability of the electrode sheet structure during long cycles, and improve the cycle performance of the battery;

[0046] The present invention adjusts the technical parameters related to the surface capacity, such as the surface density of the first film layer and the second film layer, the mass proportion of the negative electrode active material, so that the negative electrode sheet satisfies the following relationship: C2×K2×L2=C1×[K1×X+G×(1-X)]×L1×α, so that the surface capacity of the second film layer is slightly larger than that of the first film layer, thereby reducing the overall polarization of the electrode sheet, helping to alleviate the problem of over-embedding of active materials, balancing the lithium ion distribution of the first film layer and the second film layer, and improving the reversible capacity.

[0047] Therefore, the present invention can effectively improve the fast charging performance and cycle stability of the silicon-graphite negative electrode while maintaining high energy density. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] Figure 1 Schematic diagram of the structure of the negative electrode sheet of the present invention.

[0049] Among them, 1 represents the negative electrode current collector, 2 represents the first film layer, and 3 represents the second film layer. DETAILED DESCRIPTION

[0050] The present invention discloses a negative electrode sheet and a battery. Those skilled in the art can refer to the content of this article and appropriately improve the process parameters to achieve it. It should be particularly noted that all similar substitutions and modifications are obvious to those skilled in the art, and they are all considered to be included in the present invention. The method and application of the present invention have been described through preferred embodiments, and relevant personnel can obviously modify or appropriately change and combine the methods and applications described herein without departing from the content, spirit and scope of the present invention to implement and apply the technology of the present invention.

[0051] In the description of the present invention, it should be noted that the terms "first", "second", etc. are only used for descriptive purposes, and do not indicate or imply relative importance.

[0052] In the description of the present invention, a list of items connected by the term "at least one of" or other similar terms may mean any combination of the listed items. For example, if items A, B are listed, the phrase "at least one of A, B" means only A; only B; or A and B. In another example, if items A, B, C are listed, the phrase "at least one of A, B, C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may include a single element or multiple elements. Item B may include a single element or multiple elements. Item C may include a single element or multiple elements.

[0053] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range or the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0054] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0055] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0056] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0057] Specifically, the present invention adopts the following technical solutions:

[0058] In a first aspect, the present invention provides a negative electrode sheet, the negative electrode sheet comprising:

[0059] (a) negative electrode current collector;

[0060] (b) a first film layer, the first film layer is disposed on at least one side of the negative electrode current collector; the first film layer comprises a first negative electrode active material, the first negative electrode active material comprises primary graphite particles and a silicon-based material;

[0061] (c) a second film layer, the second film layer is arranged on a surface of the first film layer away from the negative electrode current collector; the second film layer includes a second negative electrode active material, and the second negative electrode active material includes secondary particle graphite.

[0062] In the present invention, on the one hand, the volume change of silicon during lithium insertion and extraction will squeeze the graphite, causing displacement of graphite particles and layered cracking, and will also cause demolding and material falling problems at the pole piece level. The primary graphite particles have greater structural strength than the secondary particles. Therefore, the present invention uses a composite material of primary graphite particles and silicon-based materials as the first negative electrode active material in the first film layer, which can reduce the structural damage of graphite and pole pieces caused by the stress brought by the silicon-based materials on the basis of improving the gram capacity of the pole piece. On the other hand, the second film layer is close to the electrolyte, lithium insertion occurs preferentially, and the lithium ion concentration around the active material particles is higher than that of the first film layer, so the material has higher kinetic requirements. Since the kinetic performance of secondary graphite particles is better than that of primary graphite particles, the present invention uses secondary graphite particles as the second negative electrode active material in the second film layer, which can improve the kinetic performance of the battery.

[0063] In an embodiment of the present invention, the negative electrode sheet satisfies the following relationship:

[0064] C2×K2×L2=C1×[K1×X+G×(1-X)]×L1×α

[0065] Wherein, C2 is the coating surface density of the second film layer,

[0066] K2 is the gram capacity of secondary graphite particles in the second film layer,

[0067] L2 is the mass proportion of the second negative electrode active material in the second film layer,

[0068] C1 is the coating surface density of the first film layer,

[0069] K1 is the gram capacity of primary graphite particles in the first film layer,

[0070] X is the mass ratio of primary graphite particles in the first film layer to the first negative electrode active material,

[0071] G is the gram capacity of the silicon-based material in the first film layer,

[0072] L1 is the mass proportion of the first negative electrode active material in the first film layer,

[0073] α is the correction coefficient.

[0074] Since the deintercalation kinetics of lithium in the first film layer is slightly lower than that of the second film layer, and the active material in the second film layer preferentially deintercalates lithium, this difference will lead to overintercalation of the active material in the second film layer and incomplete intercalation of lithium in the first film layer, thereby causing reversible capacity decay. When the negative electrode sheet of the present invention satisfies the above relationship, it can ensure that the surface capacity of the second film layer is slightly greater than the surface capacity of the first film layer, which helps to alleviate the problem of overintercalation of active materials and balance the lithium ion distribution of the first film layer and the second film layer.

[0075] As a preferred value, the value range of C2 is 50-100 g / m 2 For example, the value range of C2 is 50 g / m 2 , 55g / m 2 , 60g / m 2 , 65g / m 2 , 70g / m 2 , 72g / m 2 , 75g / m 2 , 80g / m 2 , 85g / m 2 , 90g / m 2 , 95g / m 2 , 100g / m 2 Any value in or any value in the range consisting of any two of the above values.

[0076] In a specific embodiment of the present invention, the value range of C2 is 58 to 85 g / m 2 .

[0077] In the embodiment of the present invention, the value range of K2 is 340-360 mAh / g. Exemplarily, the value range of K2 is any value among 340 mAh / g, 342 mAh / g, 344 mAh / g, 346 mAh / g, 348 mAh / g, 350 mAh / g, 352 mAh / g, 354 mAh / g, 356 mAh / g, 358 mAh / g, 360 mAh / g or any value within the range formed by any two of the above values.

[0078] In the embodiment of the present invention, the value range of L2 is 95% to 97%. Exemplarily, the value range of L2 is any value among 95%, 95.2%, 95.4%, 95.6%, 95.8%, 96%, 96.2%, 96.4%, 96.6%, 96.8%, 97%, or any value within the range formed by any two of the above values.

[0079] As a preferred value, the value range of C1 is 30 to 60 g / m 2 For example, the value range of C1 is 30 g / m 2 , 35g / m 2 , 40g / m 2 , 43.5g / m 2 , 45g / m 2 45.5g / m 2 , 50g / m 2 , 55g / m 2 , 57g / m 2 , 60g / m 2Any value in or any value in the range consisting of any two of the above values.

[0080] In the specific implementation of the present invention, the value range of C1 is 30 to 57 g / m 2 .

[0081] Preferably, the value of C2 / C1 is 1 to 3. Exemplarily, the value of C2 / C1 is any value among 1.0, 1.04, 1.2, 1.4, 1.5, 1.52, 1.54, 1.56, 1.57, 1.58, 1.6, 1.62, 1.64, 1.66, 1.68, 1.7, 2.0, 2.2, 2.4, 2.6, 2.8, 2.83, 3.0 or any value within the range consisting of any two of the above values.

[0082] In a specific embodiment of the present invention, the value of C2 / C1 is 1.04 to 2.83.

[0083] In the embodiment of the present invention, the value range of K1 is 340-360 mAh / g. Exemplarily, the value range of K1 is any value among 340 mAh / g, 342 mAh / g, 344 mAh / g, 346 mAh / g, 348 mAh / g, 350 mAh / g, 352 mAh / g, 354 mAh / g, 356 mAh / g, 358 mAh / g, 360 mAh / g or any value within the range formed by any two of the above values.

[0084] In the embodiment of the present invention, the value range of X is 0.5 to 0.97. Exemplarily, the value range of X is any value among 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, 0.97 or any value within the range formed by any two of the above values.

[0085] In the embodiment of the present invention, the value range of G is 1300-1700 mAh / g. Exemplarily, the value range of G is any value among 1300 mAh / g, 1350 mAh / g, 1400 mAh / g, 1450 mAh / g, 1500 mAh / g, 1550 mAh / g, 1600 mAh / g, 1650 mAh / g, 1700 mAh / g or any value within the range formed by any two of the above values.

[0086] In the embodiment of the present invention, the value range of L1 is 94.2% to 95.7%. Exemplarily, the value range of L1 is any value among 94.2%, 94.4%, 94.6%, 94.8%, 95%, 95.2%, 95.4%, 95.6%, 95.7% or any value within the range formed by any two of the above values.

[0087] In an embodiment of the present invention, the value range of α is 1.01 to 1.06. Exemplarily, α is any value among 1.01, 1.02, 1.03, 1.04, 1.05, 1.06 or any value within the range of any two of the above values. Since the deintercalation kinetics of lithium in the first film layer is slightly lower than that of the second film layer, and the active material of the second film layer is preferentially deintercalated with lithium, this difference will lead to overintercalation of the active material in the second film layer and incomplete lithium intercalation in the first film layer, thereby causing reversible capacity decay. α within the above range can ensure that the surface capacity of the second film layer is slightly larger than that of the first film layer, which helps to alleviate the problem of overintercalation of active materials and balance the lithium ion distribution between the first film layer and the second film layer.

[0088] Preferably, the primary graphite particles are carbon-coated primary graphite particles. After carbon coating, the dynamic performance of the primary graphite particles can be further improved. Moreover, when the secondary graphite particles in the second film layer are also carbon-coated, the carbon coating of the primary graphite particles can also reduce the dynamic difference between the first film layer and the second film layer, and balance the potential distribution of the entire electrode.

[0089] Preferably, the carbon-coated primary graphite particles have a particle coating degree of >50%, a carbon coating amount of >2%, and a particle size D 50 6 to 10 μm. Exemplarily, the carbon coating amount of the carbon-coated primary graphite particles is any value among 2.5%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, or any value within the range of any two of the above values. Exemplarily, the particle size D of the carbon-coated primary graphite particles is 50 It is any value among 6μm, 7μm, 8μm, 9μm, 10μm, or any value within the range consisting of any two of the above values.

[0090] In an embodiment of the present invention, the silicon-based material includes a silicon-oxygen material and / or a silicon-carbon composite material.

[0091] As a preference, the particle size D of the silicon-based material 50 For example, the particle size D of the silicon-based material is 6 to 10 μm. 50 It is any value among 6μm, 7μm, 8μm, 9μm, 10μm, or any value within the range consisting of any two of the above values.

[0092] Preferably, the silicon-based material accounts for 3% to 50% of the total mass of the first negative electrode active material. Exemplarily, the silicon-based material accounts for any of 3%, 4%, 6%, 8%, 10%, 12%, 14%, 16%, 18%, 20%, 22%, 24%, 26%, 28%, 30%, 32%, 34%, 36%, 38%, 40%, 42%, 44%, 46%, 48%, 50% of the total mass of the first negative electrode active material, or any value within the range of values ​​composed of any two of the above values. When it is greater than this range, the structural damage of the pole piece level caused by the expansion of excessive silicon-based material embedded lithium will lead to the rapid attenuation of the battery performance. If it is less than this range, the energy density advantage brought by the use of silicon-based materials cannot be brought into play.

[0093] Preferably, the secondary graphite particles are carbon-coated secondary graphite particles. After carbon coating, the dynamic performance of the secondary graphite particles can be further improved.

[0094] Preferably, the carbon-coated secondary graphite particles have a particle coating degree of >50% and a carbon coating amount of >2%. Exemplarily, the carbon coating amount of the carbon-coated secondary graphite particles is any value among 2.5%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, or any value within the range consisting of any two of the above values.

[0095] In an embodiment of the present invention, the first film layer includes the following components in percentage by weight:

[0096] The first negative electrode active material is 94.2% to 95.7%;

[0097] The first conductive agent is 1.5% to 1.7%;

[0098] The first binder is 2.8% to 5%.

[0099] In an embodiment of the present invention, the second film layer includes the following components in proportion by weight:

[0100] The second negative electrode active material is 95% to 97%;

[0101] The second conductive agent is 1% to 1.5%;

[0102] The second binder is 2% to 3.5%.

[0103] Preferably, the mass proportion of the first binder in the first film layer is greater than the mass proportion of the second binder in the second film layer. Since the particle volume expansion of the silicon-based material in the first film layer is much greater than that of the primary graphite particles, the first film layer requires greater adhesion to maintain the charge connectivity between the active material particles, thereby ensuring that the gram capacity is fully utilized while reducing electrical insulation and lithium precipitation.

[0104] In an embodiment of the present invention, the first conductive agent and the second conductive agent independently include at least one of conductive carbon black (Super P), vapor generated carbon fiber (VGCF), graphene, and carbon nanotubes (CNTs).

[0105] Preferably, the first conductive agent comprises carbon nanotubes, and the mass proportion of carbon nanotubes in the first film layer is 0-0.08%. The linear structure of carbon nanotubes can greatly enhance the long-range transmission of electrons in the electrode piece, compensating for the polarization of the electrode layer caused by the poor conductivity of silicon-based materials.

[0106] Preferably, the first adhesive and the second adhesive are both aqueous adhesives.

[0107] In an embodiment of the present invention, the first binder and the second binder independently include at least one of styrene-butadiene rubber (SBR), nitrile rubber, butadiene rubber, modified styrene-butadiene rubber, sodium carboxymethyl cellulose (CMC-Na), polyacrylic acid (PAA), sodium polyacrylate (PAA-Na), water-based polyacrylonitrile copolymer, and polyacrylate.

[0108] In an embodiment of the present invention, the negative electrode current collector is one of a homogeneous copper foil, a porous copper foil, and a copper foil with a carbon coating layer.

[0109] In a second aspect, the present invention provides a battery comprising the negative electrode sheet described above.

[0110] In the embodiment of the present invention, the battery structure includes but is not limited to button batteries, soft-pack batteries, cylindrical batteries, etc.

[0111] The present application has no particular restrictions on the positive electrode sheet, separator, and electrolyte in the battery, and those skilled in the art can select them according to actual needs as long as the purpose of the present application can be achieved.

[0112] The reagents, instruments or materials used in the present invention can be obtained through commercial channels.

[0113] The present invention will be further described below in conjunction with embodiments:

[0114] Embodiment 1:

[0115] 1. Preparation of negative electrode sheet:

[0116] a) Preparation of the first film layer

[0117] The first negative electrode active material (a mixture of carbon-coated primary particles of artificial graphite and pre-lithium silicon oxide material, with a mass ratio of 8:2), conductive carbon black Super P (SP), single-walled carbon nanotubes (SWCNT), polyacrylic acid (PAA), and styrene-butadiene rubber (SBR) are mixed in a mass ratio of 95.7%: 1.42%: 0.08%: 1.9%: 0.9%, and deionized water is added and stirred into a uniform slurry to obtain a first film layer slurry. Among them, the carbon coating amount of the primary particles of artificial graphite is 3%, and the particle coating degree is >50%; the D of the primary particles of artificial graphite and the pre-lithium silicon oxide material is 1.42%: 0.08%: 1.9%: 0.9%. 50 Both are 8μm.

[0118] The first film layer slurry was evenly coated on both sides of the negative electrode current collector (8 μm copper foil), and the coating surface density of the first film layer was 45 g / m 2 .

[0119] b) Preparation of the second film layer

[0120] The second negative electrode active material (carbon-coated secondary particle artificial graphite, carbon coating amount is 3%, particle coating degree>50%), SP, PAA, SBR are mixed in a mass ratio of 97%:1%:1.3%:0.7%, deionized water is added and stirred into a uniform slurry to obtain a second film layer slurry.

[0121] The second film layer slurry is evenly coated on the first film layer. The coating surface density of the second film layer is 70.46 g / m 2 .

[0122] c) Preparation of negative electrode sheet

[0123] After drying and cold pressing, the negative electrode sheet is obtained. The structural diagram is shown in Figure 1 As shown, the compacted density is 1.6g / cm 3 .

[0124] 2. Preparation of positive electrode:

[0125] The positive electrode active material (ternary nickel cobalt manganese oxide LiNi 0.8 Co 0.1 Mn 0.1 ), SP, carbon nanotubes, and binder PVDF5130 were mixed in a ratio of 97:1.6:0.4:1, and NMP was added and stirred to form a uniform and stable positive electrode slurry. The positive electrode slurry was evenly coated on the positive electrode current collector (13μm aluminum foil) with a coating surface density of 195g / m 2 After drying and cold pressing, the positive electrode sheet was obtained with a compaction density of 3.4 g / cm 3 .

[0126] 3. Selection of isolation membrane:

[0127] Polypropylene film is selected as the isolation film base film with a thickness of 12 μm.

[0128] 4. Battery cell assembly process:

[0129] Arrange the positive electrode sheet, separator, negative electrode sheet and separator in sequence, and use winding as the assembly method.

[0130] 5. Preparation of electrolyte:

[0131] LiPF6 was dissolved in a solvent of ethylene carbonate, ethyl methyl carbonate and diethyl carbonate in a volume ratio of 1:1:1, and the concentration of LiPF6 was 1.2 mol / L.

[0132] 6. Preparation of batteries:

[0133] The electrolyte was injected into the dry battery cell, and after soaking for 24 hours, the battery cell was formed at 45°C. The formation process was as follows: charge at 0.05C to 3.4V, and then charge at 0.2C to 3.75V. The battery cell was completed after aging at room temperature for 24 hours.

[0134] Embodiment 2:

[0135] The difference between this embodiment and embodiment 1 is that the formulas of the first film layer and the second film layer of the negative electrode sheet are different.

[0136] The formula of the first film layer is: first negative electrode active material: SP: SWCNT: PAA: SBR = 94.2%: 1.64%: 0.06%: 2.8%: 1.3%;

[0137] The formula of the second film layer is: second negative electrode active material: SP: PAA: SBR = 96%: 1%: 2%: 1%.

[0138] Embodiment 3:

[0139] The difference between this embodiment and embodiment 1 is that the coating surface densities of the first film layer and the second film layer are different.

[0140] The first film layer coating area density is 43.7 g / m 2 ;

[0141] The second film layer coating surface density is 71.82 g / m 2 .

[0142] Embodiment 4:

[0143] The present embodiment is different from the embodiment 1 in that the coating surface densities of the first film layer and the second film layer are different, and the formulations of the first film layer and the second film layer of the negative electrode sheet are different.

[0144] The first film layer coating surface density is 43.5g / m 2 ;

[0145] The second film layer coating surface density is 70g / m 2 ;

[0146] The formula of the first film layer is: first negative electrode active material: SP: SWCNT: PAA: SBR = 94.2%: 1.64%: 0.06%: 2.8%: 1.3%;

[0147] The formula of the second film layer is: second negative electrode active material: SP: PAA: SBR = 95%: 1.5%: 2.3%: 1.2%.

[0148] Embodiment 5:

[0149] The difference between this embodiment and embodiment 1 is that the coating surface densities of the first film layer and the second film layer are different, and the formula of the first film layer of the negative electrode sheet is different.

[0150] The first film layer coating surface density is 45.5g / m 2 ;

[0151] The second film layer coating surface density is 72g / m 2 ;

[0152] The formula of the first film layer is: first negative electrode active material: SP: SWCNT: PAA: SBR = 95%: 1.53%: 0.07%: 2.3%: 1.1%.

[0153] Embodiment 6:

[0154] This embodiment is different from the embodiment 1 in that the gram capacity of the graphite and silicon oxide material used is different, and the mixing ratio of the graphite and silicon oxide material in the first film layer is different. The gram capacity of the primary graphite particles used in the embodiment 6 is 340mAh / g, the gram capacity of the secondary graphite particles is 360mAh / g, and the gram capacity of the pre-lithium silicon oxide material used is 1300mAh / g; the negative electrode active material in the first film layer is a mixture of carbon-coated primary particles of artificial graphite and pre-lithium silicon oxide material, with a mass ratio of 9.7:0.3; the formula and process of the first film layer and the second film layer are the same as those in the embodiment 1.

[0155] The first film layer coating surface density is 56.5g / m 2 ;

[0156] The second film layer coating area density is 58.5g / m 2 .

[0157] Embodiment 7:

[0158] The difference between this embodiment and embodiment 1 is that the gram capacity of the silicon oxide material used is different, and the mixing ratio of graphite and silicon oxide material in the first film layer is different. The gram capacity of the pre-lithium silicon oxide material used in embodiment 7 is 1700mAh / g. In embodiment 7, the negative electrode active material of the first film layer is a mixture of carbon-coated primary particles of artificial graphite and pre-lithium silicon oxide material, with a mass ratio of 5:5. The formula of the first film layer is, the first negative electrode active material: SP: SWCNT: PAA: SBR = 94.2%: 1.53%: 0.07%: 2.8%: 1.4%.

[0159] The first film layer coating surface density is 30g / m 2 ;

[0160] The second film layer coating surface density is 85g / m 2 .

[0161] Comparative Example 1:

[0162] The difference between this comparative example and Example 1 is that the negative electrode sheet includes one film layer.

[0163] The negative electrode active material (a mixture of carbon-coated primary particles of artificial graphite, carbon-coated secondary particles of artificial graphite and pre-lithium silicon oxide material, the mass ratio of the three is 4.5:4.5:1), SP, SWCNT, PAA, and SBR are mixed in a mass ratio of 95.7%:1.42%:0.08%:1.9%:0.9%, deionized water is added and stirred into a uniform slurry to obtain a membrane layer slurry.

[0164] The film slurry was evenly coated on the negative electrode current collector (8 μm copper foil), and the coating surface density of the film layer was 115.46 g / m 2 .

[0165] Comparative Example 2:

[0166] The difference between this comparative example and Example 1 is that the negative electrode sheet is the negative electrode sheet of Example 1 in which the two film layers are interchanged.

[0167] a) Preparation of the first film layer

[0168] The first negative electrode active material (carbon-coated secondary particle artificial graphite, carbon coating amount is 3%, particle coating degree>50%), SP, PAA, SBR are mixed in a mass ratio of 97%:1%:1.3%:0.7%, deionized water is added and stirred into a uniform slurry to obtain a first film layer slurry.

[0169] The first film layer slurry was evenly coated on the negative electrode current collector (8 μm copper foil), and the coating surface density of the first film layer was 70.46 g / m 2 .

[0170] b) Preparation of the second film layer

[0171] The second negative electrode active material (a mixture of carbon-coated primary particles of artificial graphite and pre-lithium silicon oxide material, the mass ratio of the two is 8:2), conductive carbon black Super P (SP), single-walled carbon nanotubes (SWCNT), polyacrylic acid (PAA), styrene-butadiene rubber (SBR) are mixed in a mass ratio of 95.7%: 1.42%: 0.08%: 1.9%: 0.9%, deionized water is added and stirred into a uniform slurry to obtain a second film layer slurry. Among them, the carbon coating amount of the primary particles of artificial graphite is 3%, and the particle coating degree is >50%; the D of the primary particles of artificial graphite and the pre-lithium silicon oxide material is 1.42%: 0.08%: 1.9%: 0.9%. 50 Both are 8μm.

[0172] The second film layer slurry is evenly coated on the first film layer. The coating surface density of the second film layer is 45g / m 2 .

[0173] c) Preparation of negative electrode sheet

[0174] After drying and cold pressing, the negative electrode sheet was obtained with a compaction density of 1.6 g / cm 3 .

[0175] Comparative Example 3:

[0176] The difference between this comparative example and Example 1 is that the negative electrode sheet is the negative electrode sheet of Example 1 in which the graphite materials of the two film layers are interchanged.

[0177] a) Preparation of the first film layer

[0178] The first negative electrode active material (a mixture of carbon-coated secondary particle artificial graphite and pre-lithium silicon oxide material, with a mass ratio of 8:2), conductive carbon black Super P (SP), single-walled carbon nanotubes (SWCNT), polyacrylic acid (PAA), and styrene-butadiene rubber (SBR) are mixed in a mass ratio of 95.7%: 1.42%: 0.08%: 1.9%: 0.9%, deionized water is added and stirred into a uniform slurry to obtain a first film layer slurry.

[0179] The first film layer slurry was evenly coated on the negative electrode current collector (8 μm copper foil), and the coating surface density of the first film layer was 45 g / m 2 .

[0180] b) Preparation of the second film layer

[0181] The second negative electrode active material (carbon-coated primary particle artificial graphite), SP, PAA, and SBR were mixed in a mass ratio of 97%:1%:1.3%:0.7%, deionized water was added and stirred into a uniform slurry to obtain a second film layer slurry.

[0182] The second film layer slurry is evenly coated on the first film layer. The coating surface density of the second film layer is 70.46 g / m 2 .

[0183] c) Preparation of negative electrode sheet

[0184] After drying and cold pressing, the negative electrode sheet was obtained with a compaction density of 1.6 g / cm 3 .

[0185] Comparative Example 4:

[0186] The difference between this comparative example and Example 1 is that the coating surface densities of the first film layer and the second film layer of the negative electrode sheet are different.

[0187] The coating area density of the first film layer is 43.2 g / m 2 ;

[0188] The coating area density of the second film layer is 72.33 g / m 2 .

[0189] Comparative Example 5:

[0190] The difference between this comparative example and Example 1 is that the coating surface densities of the first film layer and the second film layer of the negative electrode sheet are different.

[0191] The coating area density of the first film layer is 45.8 g / m 2 ;

[0192] The coating area density of the second film layer is 69.59 g / m 2 .

[0193] Comparative Example 6:

[0194] The difference between this comparative example and Example 6 is that the negative electrode sheet includes a film layer.

[0195] The negative electrode active material (a mixture of carbon-coated primary particles of artificial graphite, carbon-coated secondary particles of artificial graphite and pre-lithium silicon oxide material, the mass ratio of the three is 4.925:4.925:0.15), SP, SWCNT, PAA, and SBR are mixed in a mass ratio of 95.7%:1.42%:0.08%:1.9%:0.9%, deionized water is added and stirred into a uniform slurry to obtain a membrane layer slurry.

[0196] The film slurry was evenly coated on the negative electrode current collector (8 μm copper foil), and the coating surface density of the film layer was 115 g / m 2 .

[0197] Comparative Example 7:

[0198] The difference between this comparative example and Example 1 is that the negative electrode sheet includes one film layer.

[0199] The negative electrode active material (a mixture of carbon-coated primary particles of artificial graphite, carbon-coated secondary particles of artificial graphite and pre-lithium silicon oxide material, the mass ratio of the three is 3.75:3.75:2.5), SP, SWCNT, PAA, and SBR are mixed in a mass ratio of 94.2%:1.53%:0.07%:2.8%:1.4%, deionized water is added and stirred into a uniform slurry to obtain a membrane layer slurry.

[0200] The film slurry was evenly coated on the negative electrode current collector (8 μm copper foil), and the coating surface density of the film layer was 90 g / m 2 , its electrode surface capacity, i.e., Q1+Q2, is the same as that in Example 7.

[0201] Battery parameter determination and performance testing

[0202] The parameters and performance tests of the batteries of the above embodiments and comparative examples were carried out as follows:

[0203] 1. Surface capacity determination

[0204] Formula (I) and formula (II) are used to calculate the surface capacity Q1 of the first membrane layer and the surface capacity Q2 of the second membrane layer respectively:

[0205] Q1=C1×[K1×X+G×(1-X)]×L1 Formula (I)

[0206] Q2=C2×K2×L2 Formula (II)

[0207] Wherein, C1 is the coating surface density of the first film layer, K1 is the gram capacity of primary graphite particles in the first film layer, X is the mass proportion of primary graphite particles in the first film layer in the first negative electrode active material, G is the gram capacity of the silicon-based material in the first film layer, and L1 is the mass proportion of the first negative electrode active material in the first film layer;

[0208] C2 is the coating surface density of the second film layer, K2 is the gram capacity of the secondary graphite particles in the second film layer, and L2 is the mass proportion of the second negative electrode active material in the second film layer.

[0209] Then use formula (III) to calculate the correction coefficient α:

[0210] α=Q2 / Q1 Formula (III)

[0211] 2. Membrane resistance test

[0212] Experimental equipment: Sheet resistor meter, model BER1300 (IEST Yuanneng Technology), electrode diameter is 14 mm.

[0213] The test method is:

[0214] 1) Do not place the negative electrode sheet on the membrane resistor meter, set the test pressure on the MRMS software, apply a pressure of 25MPa, hold the pressure for 25s, click to start the test, and click to return to zero after the result appears.

[0215] 2) Cut the rolled negative electrode sheet into a rectangular size of about 5cm×10cm, place it between the two electrodes of the membrane resistance meter, set the test parameters on the MRMS software, and the pressure and holding time are the same as step 1), and start the test. The software automatically reads the thickness, resistance, resistivity, conductivity and other data of the negative electrode sheet. Six positions are randomly selected for each negative electrode sheet for testing, and the average value is the membrane resistance value of the negative electrode sheet.

[0216] 3. Full charge rebound rate test

[0217] 1) Use a micrometer to measure the negative electrode sheet after rolling, and record the thickness of the negative electrode sheet as C1;

[0218] 2) Charge the divided battery to 100% SOC at a charging current of 1C according to the standard test process, disassemble the fully charged battery, measure the fully charged negative electrode sheet with a micrometer, and record the electrode sheet thickness as C2;

[0219] 3) Full charge rebound rate = (C2-C1) / C1×100%.

[0220] 4. First-effect (first efficiency) test

[0221] 1) In a 25°C constant temperature box, charge the battery to 4.25V at 1C constant current, let it stand for 30 minutes, then charge it to 4.25V at 0.2C constant current, and record the total charge capacity A;

[0222] 2) After standing for 30 minutes, discharge at a constant current of 1C to 2.5V and record the discharge capacity B;

[0223] 3) First effect = B / A × 100%.

[0224] 5. Cycle test

[0225] 1) Place in a 25℃ constant temperature box for 30 minutes and charge to 4.25V at 1C constant current;

[0226] 2) After standing for 30 minutes, discharge at a constant current of 1C to 2.5V and record the initial discharge capacity C1;

[0227] 3) Cycle 1) to 2) until the discharge capacity of the battery is less than 80% of the initial discharge capacity C1, then stop the test and record the discharge capacity Cn, where n is the number of cycles; capacity retention rate after n cycles = discharge capacity Cn / initial discharge capacity × 100%.

[0228] 6. DCR growth rate test

[0229] 1) At 25°C, charge the battery to 4.25V at 1C constant current;

[0230] 2) After standing for 30 minutes, discharge at 1C constant current for 30 minutes (adjust to 50% SOC);

[0231] 3) Let stand for 60 minutes;

[0232] 4) Discharge at 2C constant current for 30s, record the open circuit voltage U1, U2 and discharge current I before and after discharge, battery DCR = (U1-U2) / I, and the battery DCR is D1;

[0233] The battery with SOC lower than 80% of the initial capacity in the 1C cycle test is subjected to DCR test again according to the process of 1) to 4), and the DCR after the cycle is D2;

[0234] DCR growth rate = (D2-D1) / D1.

[0235] The determination and test results are shown in the following table.

[0236] Table 1 Surface capacity of the first film layer

[0237]

[0238] Note: C1 is the coating surface density of the first film layer, K1 is the gram capacity of the primary graphite particles in the first film layer, X is the mass proportion of the graphite particles in the first film layer (Examples 1-7 and Comparative Example 3 are primary graphite particles, and Comparative Example 1, Comparative Example 6 and Comparative Example 7 are the sum of primary graphite particles and secondary graphite particles) in the first negative electrode active material, G is the gram capacity of the silicon-based material in the first film layer, L1 is the mass proportion of the first negative electrode active material in the first film layer, and Q1 is the surface capacity of the first film layer.

[0239] Table 2 Surface capacity of the second membrane layer

[0240]

[0241]

[0242] Note: C2 is the coating surface density of the second film layer, K2 is the gram capacity of the secondary graphite particles in the second film layer, L2 is the mass proportion of the second negative electrode active material in the second film layer, and Q2 is the surface capacity of the second film layer. The calculation formula corresponding to the K2 value of Comparative Example 2 in Table 2 is actually K2×X+G×(1-X).

[0243] Table 3

[0244] Group <![CDATA[Q1]]> <![CDATA[Q2]]> α Example 1 23686 23921 1.01 Example 2 23315 23675 1.02 Example 3 23001 24383 1.06 Example 4 22537 23275 1.03 Example 5 23774 24444 1.03 Example 6 19941 20428 1.02 Example 7 28967 29401 1.02 Comparative Example 1 49723 / / Comparative Example 2 23921 21533 0.90 Comparative Example 3 23686 23921 1.01 Comparative Example 4 22738 24556 1.08 Comparative Example 5 24107 23626 0.98 Comparative Example 6 40088 / / Comparative Example 7 58286 / /

[0245] Table 4 Performance test results

[0246]

[0247]

[0248] From the membrane resistance data, Examples 1 to 5 are better than Comparative Examples 1 to 5. Among them, after the content of the conductive agent in the formula of Example 2 is increased, the membrane resistance is reduced compared with Example 1; the surface capacity of the second membrane layer of Example 3 is slightly increased compared with Example 1, resulting in a slight decrease in its membrane resistance, but the overall difference is not large. Comparative Example 4 has a larger overall proportion of graphite in the electrode than the other comparative examples, and its membrane resistance is also improved.

[0249] Judging from the first efficiency data of the battery cells, there is little difference between the embodiments and the comparative examples as a whole, which is mainly due to the same active materials. The first efficiency of comparative examples 1 to 5 is slightly lower, which is mainly due to the hysteresis of the electrochemical reaction caused by polarization, resulting in incomplete delithiation of some silicon-based materials at low SOC.

[0250] From the perspective of full charge rebound, Examples 1 to 5 are significantly better than Comparative Examples 1 to 5, which is mainly due to the layered design and the high strength of the primary graphite particles, which reduce the damage to the pole piece structure caused by the volume expansion of silicon.

[0251] From the cycle and DCR growth data, Examples 1 to 5 are significantly better than Comparative Examples 1 to 5. Among them, the cycle performance of Comparative Examples 2 to 5 is better than that of Comparative Example 1, which proves that the design of the layered structure effectively improves the stability of the pole piece structure during long cycles; and the DCR growth of Examples 1 to 5 is better than that of Comparative Examples 4 to 5, which proves that when the surface density of the first film layer and the second film layer is within the constraint conditions, the polarization of the pole piece as a whole will be further reduced.

[0252] Compared with Example 1, since Comparative Example 1 does not adopt a layered structure design, the volume expansion of silicon due to the lack of constraints from the surface material area will damage the overall structural compactness of the electrode and aggravate the electrical insulation and demolding phenomena during the cycle. In addition, due to the differences in gram capacity and lithium insertion speed between graphite and silicon, an electric potential difference will be generated inside the electrode, reducing the fast charging and power performance.

[0253] Compared with Example 1, in Comparative Example 2, since the first film layer and the second film layer are swapped in position, silicon is located on the surface of the negative electrode, and the pole piece rebound caused by lithium insertion expansion is larger than that of the single-layer pole piece, and its full charge rebound rate is the maximum among all the embodiments and comparative examples. This loose pole piece structure will cause breakpoints in the electrical connection between the conductive agent and the active material, and accelerate the failure of the binder in the second film layer, resulting in cycle deterioration; and the contact between silicon and the surface electrolyte will produce side reactions, further reducing the first effect and cycle performance.

[0254] Compared with Example 1, in Comparative Example 3, since the positions of the primary graphite particles and the secondary graphite particles are swapped, the primary particles are close to the electrolyte in the second film layer. Since the fast charging ability of the primary particles is smaller than that of the secondary particles, their lithium insertion speed is lower than that of the secondary particles when facing a large number of lithium ions, and the purpose of reducing the overall potential difference of the electrode plate cannot be achieved, polarization occurs, resulting in an aggravated increase in DCR and poor cycle performance.

[0255] Compared with Example 1, in Comparative Example 4, since α is greater than 1.06, the surface capacity difference between the upper and lower layers is relatively large. Due to the long migration distance of lithium ions through the second film layer to the first film layer, lithium ions are preferentially embedded in the second film layer, and the first film layer will have the phenomenon of incomplete lithium embedding of materials. During the cycle, the incomplete lithium embedding of silicon will cause the loss of active lithium and the cycle will deteriorate.

[0256] Compared with Example 1, in Comparative Example 5, since α is less than 1.01, lithium is preferentially embedded in the second membrane layer close to the electrolyte, and the low capacity of the second membrane layer will lead to over-embedding of graphite, thereby causing graphite cracking, increased polarization, and increased growth of membrane resistance and DCR, resulting in poor cycle performance.

[0257] Examples 6 and 7 are electrochemical systems with different energy densities from Example 1. Compared with Comparative Example 6, Example 6 and Example 7, respectively, have improved kinetics and cycle life, proving that the present invention is applicable to different graphite-doped silicon systems and has effective performance improvements.

[0258] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A negative electrode sheet, characterized in that: The negative electrode sheet comprises: (a) negative electrode current collector; (b) a first film layer, the first film layer being disposed on at least one side of the negative electrode current collector; the first film layer comprising a first negative electrode active material, the first negative electrode active material comprising primary graphite particles and a silicon-based material; (c) a second film layer, the second film layer is arranged on a surface of the first film layer on a side away from the negative electrode current collector; the second film layer includes a second negative electrode active material, and the second negative electrode active material includes secondary particle graphite.

2. The negative electrode sheet according to claim 1, characterized in that: The negative electrode sheet satisfies the following relationship: C2×K2×L2=C1×[K1×X+G×(1-X)]×L1×α Wherein, C2 is the coating surface density of the second film layer, K2 is the gram capacity of secondary graphite particles in the second film layer, L2 is the mass proportion of the second negative electrode active material in the second film layer, C1 is the coating surface density of the first film layer, K1 is the gram capacity of primary graphite particles in the first film layer, X is the mass ratio of primary graphite particles in the first film layer to the first negative electrode active material, G is the gram capacity of the silicon-based material in the first film layer, L1 is the mass proportion of the first negative electrode active material in the first film layer, α is the correction coefficient.

3. The negative electrode sheet according to claim 2, characterized in that: The value range of K2 is 340~360mAh / g, The value range of L2 is 95% to 97%. The value range of K1 is 340~360mAh / g, The value range of X is 0.5 to 0.

97. The value range of G is 1300~1700mAh / g, The value range of L1 is 94.2% to 95.7%, The value range of α is 1.01 to 1.

06.

4. The negative electrode sheet according to any one of claims 1 to 3, characterized in that: The primary graphite particles are carbon-coated primary graphite particles; The carbon-coated primary graphite particles have a particle coating degree of >50%, a carbon coating amount of >2%, and a particle size D 50 6~10μm.

5. The negative electrode sheet according to any one of claims 1 to 4, characterized in that: The silicon-based material includes silicon-oxygen material and / or silicon-carbon composite material; The particle size D of the silicon-based material 50 6~10μm.

6. The negative electrode sheet according to any one of claims 1 to 5, characterized in that: The silicon-based material accounts for 3% to 50% of the total mass of the first negative electrode active material.

7. The negative electrode sheet according to any one of claims 1 to 6, characterized in that: The secondary graphite particles are carbon-coated secondary graphite particles; The carbon-coated secondary graphite particles have a particle coating degree of >50% and a carbon coating amount of >2%.

8. The negative electrode sheet according to any one of claims 1 to 7, characterized in that: The first film layer includes the following components in proportion by weight: The first negative electrode active material is 94.2% to 95.7%; The first conductive agent is 1.5% to 1.7%; The first binder 2.8% to 5%; The second film layer includes the following components in proportion by weight: The second negative electrode active material is 95% to 97%; The second conductive agent is 1% to 1.5%; The second binder is 2% to 3.5%.

9. The negative electrode sheet according to claim 8, characterized in that: The mass proportion of the first adhesive in the first film layer is greater than the mass proportion of the second adhesive in the second film layer.

10. A battery, characterized in that: The battery comprises the negative electrode sheet according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Secondary battery, method for preparing same, and battery module, battery pack and device including same

    CN114747042A

  • Negative pole piece as well as preparation method and application thereof

    CN114927643A

  • Silicon-based negative pole piece, preparation method thereof and lithium ion battery

    CN116387448A

  • Anode plate of lithium ion battery, preparation method of anode plate and lithium ion battery

    CN117855460A

  • Negative pole piece, battery and electric device

    CN118919642A

Cited By

  • Negative plate and battery

    CN122314777A

  • Negative electrode and battery

    CN122314777B